A prospective observational study to compare the efficacy and safety of spinal Vs general anesthesia for laparoscopic cholecystectomy - Subbiah, Venkatesh; Kumar Palaniappan, Selva (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2018)
Background: Laparoscopic cholecystectomy is usually performed under General anesthesia, but in recent times many studies have proposed spinal anesthesia as a cost-effective alternative mode of anesthesia, specially for resource poor settings with comparable efficacy, safety. But there is a scarcity of literature on the subject. Hence the current study was conducted with an objective of comparing the efficacy and safety of spinal anesthesia, as compared to general anesthesia. Materials and Methods: The current study was prospective observational study, conducted in the department of general surgery and anesthesia, Velammal medical college, Madurai between April to December 2017. The study has included adult patients more than 18 years of age, with ASA grade I and II, posted for laparoscopic cholecystectomy. All the patients in the study period were administered with anesthesia as per their preference after explaining the pros and cons of each procedure. Results: A total of 73 subjects were included in the final analysis, with 28 subjects in spinal anesthesia group and 45 subjects in general anesthesia group. The median postoperative VAS score was statistically significantly lesser in spinal anesthesia group till 4-hour post-operative period, compared to general anesthesia group. After 4 hours the median VAS score was comparable between two groups. The ease of performing surgery score was similar in both the groups (2.630.62 in SA and 2.570.49 in GA, P value 0.647). The mean duration of surgery was also comparable between two groups (89.5629.42 minutes in SA and 86.6731.07minutes in GA, P value 0.694). Among the spinal anaesthesia group, 6(21.42%) had shoulder pain, 2(7.14%) had intraoperative nausea/vomiting, 9(32.14%) had hypertension. None of the GA group had intraoperative complications. The proportion of subjects with a post-operative headache was 25% and 17.78% in SA and GA group respectively (P value 0.61). The proportion of people with post-operative nausea and vomiting was 14.2% and 37.7% % in SA and GA groups respectively (P value 0.031). Conclusions: Spinalanaesthesia is a safe and effective alternative to general anaesthesia to perform laparoscopic cholecystectomy.